Pasteurised milk and implementation of HACCP (Hazard Analysis Critical Control Point) - Murdiati, T.B; Priadi, A; Rachmawati, S; ., Yuningsih (Indonesian Journal of Animal and Veterinary Sciences, 2004)
The purpose of pasteurisation is to destroy pathogen bacteria without affecting the taste, flavor, and nutritional value. A study on the implementation of HACCP (Hazard Analysis Critical Control Point) in producing pasteurized milk was carried out in four processing unit of pasteurised milk, one in Jakarta, two in Bandung and one in Bogor. The critical control points in the production line were identified. Milk samples were collected from the critical points and were analysed for the total number of microbes. Antibiotic residues were detected on raw milks. The study indicated that one unit in Bandung dan one unit in Jakarta produced pasteurized milk with lower number of microbes than the other units, due to better management and control applied along the chain of production. Penisilin residues was detected in raw milk used by unit in Bogor. Six critical points and the hazard might arise in those points were identified, as well as how to prevent the hazards. Quality assurance system such as HACCP would be able to produce high quality and safety of pasteurised milk, and should be implemented gradually. Â  Key words: Pasteurised milk, food safety, HACCP